Permeability and microstructure of pyrolysis lignite - Yajun LI; Qiaorong MENG; Tao CHEN; Feng LIN (Meitan xuebao, 2023)
In order to study the influence of micro pore fissure structure on permeability under the thermal-fluid-solid coupling during lignite pyrolysis, real-time CT scanning of lignite during low-temperature pyrolysis was carried out by using the μCT225kVFCB high-precision micro-CT test system of Taiyuan University of Technology, combined with the self-developed high-temperature atmosphere furnace. The micro-structure of lignite was studied and analyzed with AVIZO software. Through the extraction and analysis of the effective pore and fissure of lignite, the evolution process of the permeability of lignite under non-stress condition with temperature was studied from the perspectives of Kozeny-Carman permeability estimation equation and Darcy’s law. The results show that: ① From room temperature to 600 ℃, the evolution process can be divided into three stages: the first stage, at room temperature to 300 ℃, thermal cracking occurs in the coal body, resulting in the generation of a large number of pores and fissures, and the permeability increases by orders of magnitude. The second stage is at 300 to 500 ℃, the coal matrix is pyrolysed and the new pyrolysis products change the fluid channels, causing a slow decrease in permeability. The third stage is at 500 to 600 ℃, permeability begins to increase again, permeability enters the next rapid increase stage. ② At 300 ℃, the permeability of lignite reaches 15.5×10−12 m2, and the coal body is basically completely penetrated. ③ Under the thermal-fluid-solid coupling, the pyrolysis permeability of lignite depends not only on the micro-structure of pores and fissures, but also on the flow characteristics of fluid in the coal matrix. With the increase of temperature, the influence of heat and mass transfer characteristics of fluid on the permeability becomes more and more obvious. ④ The permeability estimated by Kozeny-Carman equation based on pore fissure structure parameters is similar to the absolute permeability, which can basically reflect the relationship between permeability and temperature. The permeability estimation based on the real pore fissure structure can greatly reduce the difficulty of seepage experiment at high temperature and pressure, and provide a method for simplifying and verifying the seepage experiment of rock mass.